2021
DOI: 10.1186/s40478-021-01204-8
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R inhibition rescues tau pathology and neurodegeneration in an A/T/N model with combined AD pathologies, while preserving plaque associated microglia

Abstract: Alzheimer's disease (AD) is characterized by a sequential progression of amyloid plaques (A), neurofibrillary tangles (T) and neurodegeneration (N), constituting ATN pathology. While microglia are considered key contributors to AD pathogenesis, their contribution in the combined presence of ATN pathologies remains incompletely understood. As sensors of the brain microenvironment, microglial phenotypes and contributions are importantly defined by the pathologies in the brain, indicating the need for their analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…Blockade of microglial proliferation by CSF1R inhibitor JNJ-40346527 (JNJ-527) attenuated tau-induced neurodegeneration in the P301S mouse tauopathy model ( Mancuso et al, 2019 ). Lodder et al (2021) revealed that pharmacological targeting of CSF1R preferentially eliminated non-plaque-associated microglia and rescued tau pathology and neurodegeneration in a combined AD pathologies mouse model, while preserving protective plaque associated microglia. Administration of PLX5622 dramatically reduced propagation of p-tau in App NL– G –F mouse, a humanized APP mutant knock-in homozygote mouse ( Clayton et al, 2021 ).…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Blockade of microglial proliferation by CSF1R inhibitor JNJ-40346527 (JNJ-527) attenuated tau-induced neurodegeneration in the P301S mouse tauopathy model ( Mancuso et al, 2019 ). Lodder et al (2021) revealed that pharmacological targeting of CSF1R preferentially eliminated non-plaque-associated microglia and rescued tau pathology and neurodegeneration in a combined AD pathologies mouse model, while preserving protective plaque associated microglia. Administration of PLX5622 dramatically reduced propagation of p-tau in App NL– G –F mouse, a humanized APP mutant knock-in homozygote mouse ( Clayton et al, 2021 ).…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, we observed a significant increment in the expression of the microglial activation marker Clec7a and a trend of increase in Trem2 and Cd45 markers after 7 days of repopulation ( Figure 1 E), which may allow the remaining microglia to be less dependent on CSF1R signaling. In this sense, Lodder et al (2021) have shown that active Aβ-associated microglia were more resistant to PLX3397 treatment [ 71 ]. Additionally, it has been described in vitro that TREM2 signaling induces the activation of Syk pathway (downstream to CSF1R), in such a way that it synergizes with the CSF1-CSF1R axis [ 72 ].…”
Section: Origin and Pattern Of Microglial Repopulationmentioning
confidence: 99%
“…While plaque-associated microglia may be protective, non-plaque-associated microglia, also in the presence of Tau pathology, could display neurotoxic functions. In this sense, it has been recently demonstrated that the preferential depletion of microglia distal to amyloid deposits significantly attenuated Tau pathology and neuronal atrophy in Tau-seeding 5xFAD/PS19 mice [ 71 ]. In this model, while Aβ-associated DAM microglia may compact amyloid plaques and limit its toxicity, non-plaque-associated microglia may contribute to Tau spread and to a pro-inflammatory environment that could mediate neuronal dysfunction.…”
Section: Do Microglia Refresh or Poison Ad Progression?mentioning
confidence: 99%
“…In transgenic AD mice, high CSF‐1R expression is found in close proximity to Aβ aggregates [ 116 , 117 ]. More recently, plaque‐associated microglia were found to be more resistant to microglia depletion by CSF‐1R inhibition than non‐plaque‐associated microglia in a mouse model displaying both Aβ and tau pathology [ 118 ]. In MS lesions, CSF‐1R expression was lower than in NAWM and in EAE mice, CSF‐1R inhibitors reduced disease severity [ 113 ].…”
Section: Introductionmentioning
confidence: 99%